Development of synthetic, self-adjuvanting, and self-assembling anticancer vaccines based on a minimal saponin adjuvant and the tumor-associated MUC1 antigen. Issue 13 (8th March 2023) - Pifferi, Carlo; Aguinagalde, Leire; Ruiz-de-Angulo, Ane; Sacristán, Nagore; Baschirotto, Priscila Tonon; Poveda, Ana; Jiménez-Barbero, Jesús; Anguita, Juan; Fernández-Tejada, Alberto
Abstract : Synthesis, immuno-evaluation in mice, and NMR studies of new, self-adjuvanting, and self-assembling tri-component vaccines based on a synthetic saponin adjuvant chemically conjugated to TA-MUC1 (glyco)peptide antigens and a helper T-cell epitope. Abstract : The overexpression of aberrantly glycosylated tumor-associated mucin-1 (TA-MUC1) in human cancers makes it a major target for the development of anticancer vaccines derived from synthetic MUC1-(glyco)peptide antigens. However, glycopeptide-based subunit vaccines are weakly immunogenic, requiring adjuvants and/or additional immunopotentiating approaches to generate optimal immune responses. Among these strategies, unimolecular self-adjuvanting vaccine constructs that do not need coadministration of adjuvants or conjugation to carrier proteins emerge as a promising but still underexploited approach. Herein, we report the design, synthesis, immune-evaluation in mice, and NMR studies of new, self-adjuvanting and self-assembling vaccines based on our QS-21-derived minimal adjuvant platform covalently linked to TA-MUC1-(glyco)peptide antigens and a peptide helper T-cell epitope. We have developed a modular, chemoselective strategy that harnesses two distal attachment points on the saponin adjuvant to conjugate the respective components in unprotected form and high yields via orthogonal ligations. In mice, only tri-component candidates but not unconjugated or di-component combinations induced significant TA-MUC1-specific IgG antibodies able to recognize the TA-MUC1 on cancer cells. NMR studies revealed the formation of self-assembled aggregates, in which the more hydrophilic TA-MUC1 moiety gets exposed to the solvent, favoring B-cell recognition. While dilution of the di-component saponin–(Tn)MUC1 constructs resulted in partial aggregate disruption, this was not observed for the more stably-organized tri-component candidates. This higher structural stability in solution correlates with their increased immunogenicity and suggests a longer half-life of the construct in physiological media, which together with the enhanced antigen multivalent presentation enabled by the particulate self-assembly, points to this self-adjuvanting tri-component vaccine as a promising synthetic candidate for further development.